C5a-Preactivated Neutrophils Are Critical for Autoimmune-Induced Astrocyte Dysregulation in Neuromyelitis Optica Spectrum Disorder - Piatek, Paweł; Domowicz, Małgorzata; Lewkowicz, Natalia; Przygodzka, Patrycja; Matysiak, Mariola; Dzitko, Katarzyna; Lewkowicz, Przemysław (Frontiers in Immunology, 2018)
Neuromyelitis optica spectrum disorder (NMOSD) is an autoimmune neuroinflammatory disease. In contrast to multiple sclerosis, autoantibodies against aquaporin-4 (AQP4) expressed on astrocytic end-feet have been exclusively detected in sera of NMOSD patients. Several lines of evidence suggested that anti-AQP4 autoantibodies are pathogenic, but the mechanism triggering inflammation, impairment of astrocyte function, and the role of neutrophils presented in NMOSD cerebrospinal fluid (CSF) remains unknown. In this study, we tested how human neutrophils affect astrocytes in the presence of anti-AQP4 Abs-positive serum derived from NMOSD patients. An in vitro model of inflammation consisted of human astrocyte line, NMOSD serum, and allogenic peripheral blood neutrophils from healthy individuals. We showed evidence of pathogenicity of NMOSD serum, which by consecutive action of anti-AQP4 Abs, complement system and neutrophils affected astrocyte function. Anti-AQP4 Ab binding astrocytes initiated two parallel complementary reactions. The first one was dependent on the complement cytotoxicity via C5b-9 complex formation, and the second one on the reverse of astrocyte glutamate pump into extracellular space by C5a-preactivated neutrophils. As a consequence, astrocytes were partially destroyed; however a major population of astrocytes polarized into proinflammatory cells which were characterized by pathological glutamate removal from extracellular space.